Meat bone ratio (MBR) potongan komersial karkas ayam Broiler dengan nanoenkapsulasi ekstrak buah Mahkota Dewa - Niati Ningsih; Taufik Ahmad Zulfian; Besse Mahbuba We Tenri Gading; Zuprizal (Universitas Sulawesi Barat, 2021)
The objective of this study was to determine the effect of supplementation nanoencapsulation of Mahkota Dewa fruit extract (NEMD) against the meat bone ratio (MBR) of the commercial part of the broiler chicken carcass. The research material was used 200 male broiler chickens aged eight days who were rearing in open house cages. The treatments consisted of drinking water without feed additives (P0; negative control), drinking water + tetracycline antibiotics (P1; positive control), drinking water + 2.5% Mahkota Dewa fruit extract (P2), drinking water + 2.5 % NEMD (P3), and drinking water + 5.0 % NEMD (P4). Parameters observed were slaughter weight, carcass weight, and MBR of the commercial part of the broiler chicken carcass. The data obtained were analyzed using a completely randomized design (CRD). Data with significant results were further tested using orthogonal contrast (P-Value < 0.05). The results showed that the use of NEMD up to 5% in drinking water did not have a significant effect on the MBR of the commercial part of the broiler chicken carcass. The 5% NEMD has not been able to work optimally to increase the MBR of the commercial part of the broiler chicken carcass.